Theoretical bases of individualization of training in wrestling - Latyshev, S. (Physical Education of Students, 2013)
Theoretical bases of individualization of training in wrestling are developed. They include the structure of organization of research, positions of conception, system of individualization of training. The system of individualization of training is designed as an aggregate of elements and subsystems, which guided mutually assist an exposure, forming, development and perfection of own style of opposing. It is marked that in the system of training activity substantially more attention is spared development of the special endurance and attended directed qualities. In the system of after training and after a competition activity an accent was displaced toward the search of facilities of more effective renewal and stimulation of the special capacity, search of new optimum rations of feed and new food additions, search of new methods of decline of weight of fighters. Tactic of conduct of duels changed in the system of competition activity, which foresees yet more rational and economy expense of energy in a fight and in a competition on the whole.